Pelatihan Pembuatan Ovoposition Trap (Ovitrap) sebagai Upaya Pengendalian Vektor Demam Berdarah Dengue di Kelurahan Purbayan RT 03 RW IX Kecamatan Baki Sukoharjo - Anggraeni Sih Prabandari; Mening Sri Darwati; Agnes Regita Pramesthi Suyono (UNIVERSITAS NGUDI WALUYO, 2022)
Dengue haemorrhagic fever (DHF) is vector borne disease transmitted by Aedes sp. mosquitos. Available data has indicated an increasing trend of DHF incidence in Indonesia. Prevention of dengue transmission relies mainly through vector control. The use of traps such as ovitrap and mosquito trap has the potential to be applied and integrated with other methods. Ovitrap is expected to be applied in the community and can assist in theÂ dengueÂ vector control program. Ovitrap can be made simply used resources available at home. The expected output of the implementation of this community service is that people possess knowledge and skills in making ovitrap. Through education and practice of making ovitrap is expected to be a container for the prevention of DHF, so that its incidence can be minimized. Twenty participants joined this program. They divided into three groups with one trainer to assisted them to make ovitrap. Lately, all participants can make ovitrap correctly. We carried out follow up program after two weeks and the results is ovitrap can work properly. Participants found larva, pupa and mosquitos in the ovitrap. It is hoped that participants can use ovitrap regularly to control Aedes sp. population in Purbayan, Baki Sukoharjo.ABSTRAKDemam berdarah dengue merupakan penyakit tular vektor yang diperantarai oleh nyamuk Aedes sp. Angka kejadiannya terus meningkat di Indonesia. Berbagai strategi pencegahan dilakukan yang berfokus pada upaya pengendalian vektor. Ovitrap merupakan perangkap nyamuk sederhana yang dapat digunakan untuk menekan populasi nyamuk Aedes sp. Ovitrap dapat dibuat secara mandiri memanfaatkan alat dan bahan yang tersedia di rumah masing-masing. Tujuan kegiatan pengabdian kepada masyarakat ini adalah memberikan pelatihan kepada masyarakat tentang cara pembuatan ovitrap. Metode yang digunakan adalah ceramah, demo pembuatan ovitrap dan praktik langsung. Kegiatan diikuti oleh 20 peserta yang dibagi menjadi 3 kelompok. Masing-masing kelompok diberikan pembimbing cara pembuatan ovitrap. Pada akhir kegiatan, seluruh peserta mampu membuat ovitrap dengan benar. Pada tahap follow up, ovitrap dapat berfungsi dengan baik, terbukti dengan ditemukannya stadium jentik, pupa dan nyamuk dewasa pada larutan di dasar ovitrap. Penggunaan ovitrap secara teratur diharapkan dapat menekan populasi nyamuk Aedes sp. di wilayah Purbayan Kecamatan Baki Sukoharjo.